Discovering Reality Feminist Perspectives on Epistemology, Metaphysics, Methodology, and Philosophy of Science - Harding, Sandra; Hintikka, Merrill B.P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1983)
Are Western epistemology, metaphysics, methodology and the philosophy of science grounded only in men's distinctive understandings of themselves, others, and nature? Does this less than human understanding distort our models of reason and of scientific inquiry? In different ways, the papers in this collection explore the evidence for these increasingly reasonable and intriguing questions. They identify how it is distinctively masculine perspectives on masculine experience which have shaped the most fundamental and formal aspects of systematic thought in philosophy and the natural and social sciences - precisely the aspects of thought believed most gender-neutral. They show how these understandings ground Aristotle's biology and metaphysics; the very definition of the problems of philosophy in Plato, Descartes, Hobbes and Rousseau; the `adversary method' which is the paradigm of philosophic and scientific reasoning; principles of individuation in philosophical ontology and the philosophy of language; individualistic assumptions in psychology; functionalism in sociological and biological theory; evolutionary theory; the methodology of political science; Marxist political economy; and conceptions of `objective inquiry' in the social and natural sciences. These essays also begin to identify for us the distictive aspects of women's experience which can provide the resources needed for the creation of a truly human understanding. Audience: The book will be of interest to those involved in epistemology, and philosophy of the natural and social sciences, as well as feminist scholars in philosophy. The work will also be of value for theorists, methodologists, and feminist scholars in the natural and social sciences.
Woman is Not a Rational Animal: On Aristotle$1 (BS Biology of Reproduction -- Aristotle and the Politicization of the Soul -- The Unit of Political Analysis: Our Aristotelian Hangover -- Have Only Men Evolved? -- Evolution and Patriarchal Myths of Scarcity and Competition -- Charlotte Perkins Gilman: Forerunner of a Feminist Social Science -- The Trivialization of the Notion of Equality -- How Can Language be Sexist? -- A Paradigm of Philosophy: The Adversary Method -- The Man of Professional Wisdom -- Gender and Science -- The Mind$1 (BS Eye -- Individualism and the Objects of Psychology -- Political Philosophy and the Patriarchal Unconscious: A Psychoanalytic Perspective on Epistemology and Metaphysics -- The Feminist Standpoint: Developing the Ground for a Specifically Feminist Historical Materialism -- Why Has the Sex/Gender System Become Visible Only Now?.s
Keywords: Philosophy and science; Philosophy of Science